Spreading of hand hygiene change package across an acute hospital - Vijo Poulose; A Punithavathi; Woo Boon Ang; Alvin Chew; Augustine Tee; Seow Yen Tan; Rajkumar Chandran; Mui Mui Tang (BMJ Open Quality)
Background A set of interventions in a hand hygiene change package was developed in a pilot ward by the end of 2017. In 2018, Changi General Hospital embarked on scaling up the change package to other wards with the intention to eventually spread the hand hygiene change package hospital-wide.Methods Changi General Hospital conducted a quality improvement project on hand hygiene with the intention to effect organisation-wide improvement in hand hygiene. Spread methodologies such as the Institute for Healthcare Improvement’s framework for Spread and various complementary spread concepts such as having an organisational strategy, which plans for spread as early as possible, and addressing social aspects of change were applied in order to scale up and spread a change package.Setting A general tertiary care hospital in Singapore.Results Overall hospital-wide hand hygiene compliance improved from a median of 66% during the pilot phase to 73% in the scale-up phase (p<0.05) to 82% during the spread phase (p<0.05).Conclusions A systematic approach to hand hygiene improvement based on spread literature successfully improved and sustained hospital-wide hand hygiene compliance. Success factors included the development of a change package that had clear guiding principles, with the intent to create proactive learning cycles within units which could be adapted to work in various contexts.